INCREASING STUDENT LEARNING ACHIEVEMENT: AN INSTRUCTIONAL LEADERSHIP APPROACH - Sukarelawan, Asep Ganjar; Komussudin, Atep; Qomusuddin, Ivan Fanani (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Instructional leadership is an important component for school principals that has a great influence on the school's vision and mission, especially in improving the quality of learning. The focus of instructional leadership lies in improving the quality of learning processes and outcomes through teacher empowerment, so that this leadership motivates and facilitates teachers in improving learning. This study aims to examine the implementation of Instructional Leadership in improving student learning achievement at SMK Informatics Dienul Islam and SMK An-Nur Ibun. The research uses a qualitative method with a case study approach, data is collected through interviews, observations, and documentation. The results show that the instructional leadership of school principals runs effectively through the formulation of vision and mission, improvement of teacher competence, supervision, learning evaluation, and the development of a conducive learning climate